A framework for knowledge management system implementation in collaborative environment for higher learning institution - Abdullah, Rusli; Selamat, Mohd. Hasan; Sahibudin, Shamsul; Alias, Rose Alinda (The Leadership Alliance Inc., 2005)
“Knowledge management (KM) system” is a phrase that is used to describe the creation of knowledge repositories, improvement of knowledge access and sharing as well as communication through collaboration, enhancing the knowledge environment and managing knowledge as an asset for an organization. In this paper, we analyze the KM concept, system and architecture; then we propose a framework of KM system implementation in collaborative environment for Higher Learning Institutions (HLI). We also discuss various issues involved in this field that will help organizations to increase productivity and quality as well as to achieve return on investment (ROI). Issues that are highlighted in this paper include how best to acquire and disseminate knowledge; how to determine the best way for approaching and acquiring knowledge effectively including motivating people to share and access knowledge through the system; how to determine metrics for evaluating KM efficiency; how to identify how people create, communicate and use knowledge; and how to create more inclusive and integrated KMS software packages.